3D/2D Perovskite Single Crystals Heterojunction for Suppressed Ions Migration in Hard X‐Ray Detection. (8th September 2021) - He, Yuhong; Pan, Wanting; Guo, Chunjie; Zhang, Huimao; Wei, Haotong; Yang, Bai
Abstract: Halide perovskites exhibit diverse properties depending on their compositions. However, integrating desired properties into one material is still challenging. Here, a facile solution‐processed epitaxial growth method to grow 2D perovskite single crystal on top of 3D perovskite single crystal, which can passivate the surface defects for improved device performance is reported. Short formamidine (FA + ) ions are replaced by long organic cations, which can fully align and cover the single crystal surface to prevent the ions migration or short FA + ions volatilization. The thickness of epitaxial layer can be finely adjusted by controlling the growth time. The defect density of single crystals heterojunction is only 3.18 × 10 9 cm −3, and the carrier mobility is 80.43 cm 2 V −1 s −1, which is greater than that of the control 3D perovskite single crystal. This study for the first time realized large area 3D/2D perovskite single crystals heterojunction, which suppressed ions migration and exhibited advanced performance in hard X‐rays detection applications. This strategy also provides a way to grow large area 2D perovskite single crystal from solution processes. Abstract : The 2D epitaxial layer of the 3D/2D perovskite single crystals heterojunction can passivate the surface defects and suppress ion migration or short formamidine FA + ion volatilization, which boost its optoelectric properties. The 3D/2D heterojunction X‐ray detector exhibits stable response to 120 kVp hard X‐rays, with the lowest detectable dose rate of 55 nGyair s −1 .